Effectiveness of Rosetta Stone Software in learning the english language promoted by UDELAS in the special english program (PEI) 2009 - Atencio, Ericka (UDELAS, 2010)
As it is well known, english is an important tool, and is one of the keys to success in today'ss world, either business or cultual. The Universidad Especilizada de las Americas works to prepare their students with best tools, and implementing the use of the Rosetta Stone software to a better level of english language acquisition is one of the strategies.